2010
DOI: 10.1002/adem.200900284
|View full text |Cite
|
Sign up to set email alerts
|

Where Does the Lithium Go? – A Study of the Precipitates in the Stir Zone of a Friction Stir Weld in a Li‐containing 2xxx Series Al Alloy

Abstract: The main strengthening precipitates of aluminum alloy 2198‐T8, which are of the T1 phase, dissolve during friction stir welding, sending many Li atoms into solid solution. The stir zone precipitates are characterized using high‐resolution transmission electron microscopy, energy dispersive spectroscopy, and selected area diffraction techniques to begin answering questions about the microstructural evolution and the relationship between microstructure and mechanical properties in friction stir welding of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…Therefore, engineering applications have significant interest in aluminium alloys with lithium content because of its great potential to simultaneously provide increased damage tolerance coupled with reduction of density . The addition of Li to Al offers the possibility to reduce substantially the weight of aeronautical alloys, once every 1%wt added to Al reduces density by 3% and increases elastic modulus by nearly 6%, in addition to enabling the formation of powerful hardeners precipitates …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, engineering applications have significant interest in aluminium alloys with lithium content because of its great potential to simultaneously provide increased damage tolerance coupled with reduction of density . The addition of Li to Al offers the possibility to reduce substantially the weight of aeronautical alloys, once every 1%wt added to Al reduces density by 3% and increases elastic modulus by nearly 6%, in addition to enabling the formation of powerful hardeners precipitates …”
Section: Introductionmentioning
confidence: 99%
“…These alloys have also paired well with FSW as a joining method to offer an intriguing combination for manufacturers to consider [17,18]. The research community has taken notice as well, with a perhaps telling amount of work being conducted on FSW of Al-Li alloys [19][20][21][22][23][24][25][26][27][28][29][30][31], with particular emphasis on 2198. Other Al-Li alloys receiving attention including 2199, viewed as a viable candidate for aircraft skin, and 2099 extrusions, which would be used to form internal structural members [32].…”
Section: Introductionmentioning
confidence: 98%
“…Although the peak aged (PA) temper of this alloy is of application interest, detailed investigation of the structure-property relationships of other temper states is required since it provides the basis for understanding the influence of process-induced microstructural changes on the post-processing properties of the alloy. For instance, it was shown that the T 1 precipitate, which is the main strengthening phase in the PA temper [1,12], dissolves, while T B phase precipitates within the grain interior and in grain boundaries during friction stir welding of peak aged AA2198 [15]. The T B phase is an equilibrium phase that occurs only in the overaged temper of Al-Li based alloy systems [8].…”
Section: Introductionmentioning
confidence: 98%